Transcriptional profile of postmortem skeletal muscle - Sanoudou, D.; Kang, P. B.; Haslett, J. N.; Han, M.; Kunkel, L. M.; Beggs, A. H. (Physiol GenomicsPhysiol GenomicsPhysiol Genomics, 2004)
Autopsy specimens are often used in molecular biological studies of disease pathophysiology. However, few analyses have focused specifically on postmortem changes in skeletal muscles, and almost all of those investigate protein or metabolic changes. Although some structural and enzymatic changes have been described, the sequence of transcriptional events associated with these remains unclear. We analyzed a series of new and preexisting human skeletal muscle data sets on approximately 12,500 genes and expressed sequence tags (ESTs) generated by the Affymetrix U95Av2 GeneChips from seven autopsy and seven surgical specimens. Remarkably, postmortem specimens (up to 46 h) revealed a significant and prominent upregulation of transcripts involved with protein biosynthesis. Additional upregulated transcripts are associated with cellular responses to oxidative stress, hypoxia, and ischemia; however, only a subset of genes in these pathways was affected. Overexpression was also seen for apoptosis-related, cell cycle regulation/arrest-related, and signal transduction-related genes. No major gene expression differences were seen between autopsy specimens with <20-h and 34- to 46-h postmortem intervals or between pediatric and adult cases. These data demonstrate that, likely in response to hypoxia and oxidative stress, skeletal muscle undergoes a highly active transcriptional, and possibly, translational phase during the initial 46-h postmortem interval. Knowledge of these changes is important for proper interpretation of gene expression studies utilizing autopsy specimens.
Sanoudou, DespinaKang, Peter BHaslett, Judith NHan, MeiKunkel, Louis MBeggs, Alan HengP01 NS040828/NS/NINDS NIH HHS/AR-44345/AR/NIAMS NIH HHS/NS-40828/NS/NINDS NIH HHS/Research Support, Non-U.S. Gov'tResearch Support, U.S. Gov't, P.H.S.2003/11/20 05:00Physiol Genomics. 2004 Jan 15;16(2):222-8. doi: 10.1152/physiolgenomics.00137.2003.
Keywords: *Transcription, Genetic; gene expression profiling; Humans; Muscle, Skeletal/*metabolism; Oligonucleotide Array Sequence Analysis; Postmortem Changes